Differential returns in Germany - Theresa Lagemann; Miriam Rehm (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2025)
This paper estimates rates of return on wealth across gross wealth groups by matching individual-level survey data with macroeconomic return data for Germany. Using machine learning for more detailed financial asset categories, we find that the average nominal rate of return on gross assets for the bottom 50% is 1%, for the upper middle 40% it amounts to about 5.4%, and for the top 10% to 6.3%. Adjusted for inflation and interest payments on loans, the average rate of return for the bottom 50% is negative. We show that an intersectional analysis of wealth returns matters, with certain socio-economic characteristics such as gender or migration background predicting the position of individuals in the wealth distribution.
Keywords: 330